Contact heat evoked potentials: Normal values and use in small‐fiber neuropathy. Issue 5 (31st March 2015) - Lagerburg, Vera; Bakkers, Mayienne; Bouwhuis, Anne; Hoeijmakers, Janneke G.J.; Smit, Arjen M.; Van Den Berg, Sofia J.M; Hordijk‐De Boer, Ineke; Brouwer‐Van Der Lee, Mardien D.G.; Kranendonk, Douwe; Reulen, Jos P.H.; Faber, Catharina G.; Merkies, Ingemar S.J.
ABSTRACT: Introduction: Contact heat evoked potentials (CHEPs) may be an objective, non‐invasive diagnostic tool in small‐fiber neuropathy (SFN). This study establishes normal CHEP values and examines their applicability in SFN patients. Methods : Standardized CHEPs were administered at the wrist and ankle. The N2 and P2 latencies and N2 –P2 peak–peak amplitude were recorded by electroencephalography. We examined healthy subjects ( n  = 97), stratified by age and gender, and SFN patients with abnormal intraepidermal nerve fiber density ( n  = 42). CHEP reproducibility and interobserver values were also investigated. Results : CHEP normative values were determined. There was a 9–16% increase in latency per centimeter of height with increasing age. Amplitudes were higher in women than men, and decreased (17–71%) with aging. Test‐retest reproducibility and interobserver values were >0.61 and >0.96, respectively. CHEPs were abnormal in 73.8% of the patients. Conclusion : In this study we have established normal values, reliability, and clinical applicability of CHEPs in SFN. Muscle Nerve, 2015 Muscle Nerve 51 :743–749, 2015